Improvement of Post-combustion Carbon Capture Process in Retrofit Case. (July 2017) - Nagy, Tibor; Moioli, Stefania; Langé, Stefano; Pellegrini, Laura A.; Mizsey, Peter
Abstract: Carbon dioxide emission, one of the core cause of global warming and other threats of nonreversible environmental effects, is in focus today. Among the several methods of CO 2 emission mitigation, post-combustion carbon capture (PCC), based on absorberdesorber systems with amine absorbents, is one of the promising alternatives. The major anthropogenic CO 2 point sources are power plants, natural gas extraction units, oil refineries, cement factories, biogas plants, etc. As these CO 2 sources can be treated with a PCC absorber-desorber system, then these two units should cope with various conditions. To maintain a desired high removal efficiency, the capture unit must work in flexible conditions. The aim of this study is to evaluate the influence of the extent of the absorption of carbon dioxide on the overall performance of the acid gas removal process, considering that, generally, as the amount of removed CO 2 increases, the separation becomes more challenging. In this work a verified computer based process model for the absorber-desorber system is used. Aspen Plus® professional flowsheet simulator is used for this purpose. Attention is paid on the proper operating parameters of a PCC absorber-desorber system for the case of increasing the CO 2 capture efficiency up to 99%. As alternative solutions for these cases different scenarios are considered: the increase of the capacity of a classic configuration of an absorber-desorber system; the introduction of a second absorber column as extending the absorption column height; the possible use of two absorbers and two desorbers working in series. This work deals with the detailed study on maximizing CO 2 removal efficiency while maintaining the minimal energy consumption for the absorbent regeneration section.